Detection of antibodies against Ornithodoros moubata salivary antigens and their association with detection of African swine fever virus in pigs slaughtered in central Uganda - Kayaga, Edrine B.; Wampande, Eddie M.; Ekakoro, John E.; Okwasiimire, Rodney; Nassali, Aisha; Ochoa, Krista; Hauser, Cole; Ndoboli, Dickson; Havas, Karyn A. (Frontiers in Veterinary Science, 2024)
Introduction: African swine fever (ASF) is an important disease of pigs in sub-Saharan Africa and Uganda and is threatening the pig population and agricultural economy of other continents. ASF virus (ASFV) can be transmitted from wild suids to domestic pigs through soft ticks of the Ornithodoros species. The aim of this study was to understand the relationship between domestic pigs' O. moubata tick exposure and ASFV status. Methods: Pigs were sampled from six abattoirs in the Kampala metropolitan area of Uganda from May 2021 through June 2022. Blood, serum, and tissue samples were collected. Serum was tested for antibodies against the rtTSGP1 salivary antigens of O. moubata ticks using an indirect ELISA assay. Blood and tissue samples from pigs were tested to detect ASFV using qPCR. Probability of tick exposure was categorized based on sample-to-positive ratio cut-off points.Results: Out of 1328 serum samples tested, there were 828 (62.3%) samples with a negligible probability; 369 (27.8%) with a medium probability; 90 (6.8%) with a high probability, and 41 (3.1%) with a very high probability of exposure to the O. moubata salivary antigen. There was a statistically significant association between the pigs' O. moubata exposure and ASFV status with a higher proportion of pigs having a very high probability of infection if they were ASFV positive by blood, tonsil, and lymph nodes.Discussion: These results suggested that tick exposure was associated with ASFV transmission in Uganda. There were ASFV qPCR positive pigs that had no O. moubata exposure as well, which highlights that pig-to-pig and indirect contact transmission still play a significant role. This work highlights the need for further work in Uganda to investigate these transmission factors related to the O. moubata tick and ASFV transmission.